MODEL-MODEL SUPERVISI KEPERAWATAN KLINIK - Supratman Supratman; Agus Sudaryanto (Universitas Muhammadiyah Surakarta, 2008)
In Indonesia, supervision still orient an 'observation'; non a tuition activity of observation and assessment; appraisal. despitefully there is no a model of clinical supervision. In some western countries have been recognized and application a model of clinical supervision where its purpose is quality of care. Models recognized by: developmental model, academic model, experiential model and 4S model. Four application model have in hospital at the UK and US because education’ degree have established with the compared to Indonesia. Beside that, nursing care delivery have also become a well established system with the nurse RN'S as role and leader.